Analisis Pendapatan dan Kontribusi Usahatani Padi Gogo (Oryza Sativa l.) Terhadap Pendapatan Rumahtangga di Desa Bubu Kecamatan Kambowa Kabupaten Buton Utara - Hariati, Hariati; Limi, Muhammad Aswar; Fyka, Samsul Alam (Department of Agribusiness, Halu Oleo University, 2018)
This research aims to: 1) know the income of usatani upland rice. 2) to know the contribution of income of upland rice farming to household income. The method used in this study through survey methods, and sampling using simple random sampling method as many as 24 people. Data analysis uses income and contribution analysis.Â The results of this study indicate that the income of rice farming gogo an average of Rp. 930.605,10 / Season Planting, while the income of family members on average is Rp. 1.883.333 / Month, so total household income of Rp. 7,466,964 / Month, and Contribution of upland rice to household income of 74.47 percent and 25.53 percent of household income.